Effects of Seasonal Conditions on Abundance of Malaria Vector Anopheles stephensi Mosquitoes, Djibouti, 2018–2021 - Alia Zayed; Manal Moustafa; Reham Tageldin; James F. Harwood (Emerging Infectious Diseases, 2023)
We describe the influence of seasonal meteorologic variations and rainfall events on Anopheles stephensi mosquito populations during a 40-month surveillance study at a US military base in Djibouti. Focusing surveillance and risk mitigation for An. stephensi mosquitoes when climatic conditions are optimal presents an opportunity for malaria prevention and control in eastern Africa.